MANAGING PARENT SATISFACTION OF PUBLIC ELEMENTARY SCHOOL ON EFFECT OF EXPECTATION AND PERCEIVED VALUE - Desianti, Lisa Chandrasari; Nurlaila, Hanik; Tukiran, Mar (Journal of Industrial Engineering & Management Research, 2021)
Usually there is no attention with regards to student's or parent’s satisfaction especially for public schools. The aim of this study is to examine how parents' satisfaction levels are influenced by their expectations and perception values, so that it can improve the quality of education through improving students or parent’s satisfaction. Research was conducted in Depok Baru 2 Public Elementary School, Depok City, Indonesia. The method of analysis uses Partial Least Squares Structural Equation Modelling (PLS-SEM). 60 data out of 72 was collected from 6th grade parents. Finding of this study showed, path coefficient of customer expectations to customer perceived value was 0.626; meanwhile path coefficient of customer expectations to customer satisfaction was -0.066; and the path coefficient of customer perceived value to customer satisfaction was 0.877. Finally, the path coefficient of customer expectation to customer satisfaction through customer value was 0.549. This proves that the existence of variable mediation of customer perceived value successfully mediated customer expectations toward customer satisfaction.